Analysing the nature of plasma and blood flow using exact roving wave solutions of fifth order rove-time equation. Issue 1 (April 2021) - Senjudarvannan, R; Revathi, A; Priyadharsini, R; Sasikumar, N P; Banupriya, K; Sudha, D
Abstract: In this paper, the nonlinear higher order differential scrupulous equations share in countless spectacles in Physics such as Fluid dynamics, Hydro dynamics, Optics, Plasma physics and so on. The exact solutions of fifth order Kaup-Kupershmit equation describe the excitations and dynamics of ionised particles such as blood and plasmas which is an essential bodily function. Here the generalised Kudrayashov method is entertained for finding the exact solutions of fifth order KdV equation and for discovering precise roving wave solutions mutable to the solitary wave solutions for Kaup-Kupershmit equation. Among the voluminous methods, generalised Kudrayashov method is very imperative and produces the knowledge of Plasma dynamics.